2022
DOI: 10.25259/ijdvl_1369_20
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional immunotherapy for non-genital warts: A systematic review and meta-analysis

Abstract: Background Intralesional immunotherapy has been reported to be effective for warts and to show good safety profiles, but this has not yet been systematically studied. Aims To determine the efficacy and safety of intralesional immunotherapy for treating non-genital warts. Methods We comprehensively searched the MEDLINE, Embase, Web of Science and Cochrane Library databases from the times of their inception to January 3, 2020. The primary outcome was the rate of complete response of all lesions. The distant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…However, response rates of 64%, 52%, and 53% observed in distant warts in the patients receiving vitamin D3 MIP, and MMR were higher than the overall rate of 51.6% reported based on previous studies. This difference was especially significant in the case of vitamin D3 where distant response rate of only 17.6% was reported based on previous studies 36 . Overall, since placebo injections with normal saline also achieved similar efficacy as immunotherapies with minimal side effects, the role of local injection trauma needs to be further addressed in future randomized case control trials.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, response rates of 64%, 52%, and 53% observed in distant warts in the patients receiving vitamin D3 MIP, and MMR were higher than the overall rate of 51.6% reported based on previous studies. This difference was especially significant in the case of vitamin D3 where distant response rate of only 17.6% was reported based on previous studies 36 . Overall, since placebo injections with normal saline also achieved similar efficacy as immunotherapies with minimal side effects, the role of local injection trauma needs to be further addressed in future randomized case control trials.…”
Section: Discussionmentioning
confidence: 85%
“…This difference was especially significant in the case of vitamin D3 where distant response rate of only 17.6% was reported based on previous studies. 36 Overall, since placebo injections with normal saline also achieved similar efficacy as immunotherapies with minimal side effects, the role of local injection trauma needs to be further addressed in future randomized case control trials. We also hypothesize that the healing with placebo have a link with psychological aspect of the patient since Cw is a viral phenomenon linked with altered immunity and stress.…”
Section: Discussionmentioning
confidence: 99%
“… Martin et al (2022) reported on intralesional therapies for plantar warts among 26 studies and 6 therapies, discussing the median cure rates for vitamin D3 (80%), bleomycin (74%), 5-FU (59%), Candida (66%), zinc sulfate (70%), and PPD (67%). Ju et al (2022) reported on intralesional immunotherapies and found a pooled 60.6% (95% CI = 54.8–66.5%) local complete response rate across MMR, Candida, vitamin D, PPD, IFN-a, MIP vaccine, bacillus Calmette–Guerin (BCG) vaccine, and 8 other therapies. Unique to their study is a reported pooled recurrence rate of 2.0% (95% CI = 1.1–2.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Intralesional therapies are an emerging and effective approach for treating recalcitrant warts, particularly those situated in challenging regions such as palmoplantar and periungual areas, which often exhibit resistance to conventional treatments ( Mattoo and Bhatia, 2018 ). Several intralesional therapies for warts have emerged, including vitamin D3; tuberculin purified protein derivative (PPD); Candida antigen (Candida); the measles, mumps, rubella (MMR) vaccine; as well as various pharmaceutical mixtures, including immunotherapeutic drugs, digoxin–furosemide combinations, and antivirals such as acyclovir ( Aldahan et al, 2016 ; Fields et al, 2020 ; Ju et al, 2022 ). Unlike various other treatment options, immunotherapeutic approaches upregulate the immune system to recognize and destroy the lesions at both the target site and distant locations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation